Hot Springs Characterisation And Geothermal Potential Study In Peninsula Malaysia From Geosciences Perspectives - Arifin, Mohd Hariri (2017)
Research works on the potentials of geothermal energy resources in the non-volcanic hot springs origins within the Peninsula Malaysia have not received the much-needed attention. This, therefore, serves as a major motivation to embark on the studies that focused on the Peninsula Malaysia areas to determine the relationship among the geological, geochemical and geophysical prospection methods for the suitability of these non-volcanic hot springs origins as potential locations for the development of geothermal energy. A total of 60 hot springs locations distributed throughout the Peninsula Malaysia has been identified. These hot springs locations were classified into three major groups, namely; the Western Belt Granite, Central Belt Granite and the Eastern Belt Granite groups were all plotted together. Classifications of these non-volcanic hot springs origin was made by the same distribution pattern of the granites pluton and also close to the contact zones between the different rock types. The most significant faults in the study area; i.e.; (Baubak, Kuala Lumpur, Terengganu, Bukit Tinggi, Lebir, Lepar and Mersing) played a major role in the hot water circulation systems within the water catchment areas respectively. The geochemical analysis of the hot springs waters, confirmed that all the hot springs waters belongs to the non-volcanic origin types. Quartz and chalcedony are the most appropriate geothermometers and consistent with the range of temperatures obtained when compared to the cations and anions geothermometers.